F‐box protein FBXO16 functions as a tumor suppressor by attenuating nuclear β‐catenin function. Issue 3 (8th March 2019) - Paul, Debasish; Islam, Sehbanul; Manne, Rajesh Kumar; Dinesh, US; Malonia, Sunil K; Maity, Biswanath; Boppana, Ramanamurthy; Rapole, Srikanth; Shetty, Praveen Kumar; Santra, Manas Kumar
Abstract: Aberrant activation of β‐catenin has been implicated in a variety of human diseases, including cancer. In spite of significant progress, the regulation of active Wnt/β‐catenin‐signaling pathways is still poorly understood. In this study, we show that F‐box protein 16 (FBXO16) is a putative tumor suppressor. It is a component of the SCF (SKP1‐Cullin1‐F‐box protein) complex, which targets the nuclear β‐catenin protein to facilitate proteasomal degradation through the 26S proteasome. FBXO16 interacts physically with the C‐terminal domain of β‐catenin and promotes its lysine 48‐linked polyubiquitination. In addition, it inhibits epithelial‐to‐mesenchymal transition (EMT) by attenuating the level of β‐catenin. Therefore, depletion of FBXO16 leads to increased levels of β‐catenin, which then promotes cell invasion, tumor growth, and EMT of cancer cells. Furthermore, FBXO16 and β‐catenin share an inverse correlation of cellular expression in clinical breast cancer patient samples. In summary, we propose that FBXO16 functions as a putative tumor suppressor by forming an SCF FBXO16 complex that targets nuclear β‐catenin in a unique manner for ubiquitination and subsequent proteasomal degradation to prevent malignancy. This work suggests a novel therapeutic strategy against human cancers related to aberrant β‐catenin activation. © 2019 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.